Pengembangan lembar kerja siswa (LKS) matematika untuk kelas VII Sekolah Menengah Pertama (SMP) pada materi aritmatika sosial - Syahputri, Iga; Sari, Riska Novia (Jurnal Pendidik Indonesia, 2021)
The main objective of this research is to develop a valid Student Worksheet (LKS) in mathematics, mainly focusing on social arithmetic. The method applied in this study is the research and development approach, involving three crucial stages: definition, design, and development. A validation questionnaire was used as the research instrument. Based on the results of validity tests conducted by three validators, after undergoing a process of revisions and improvements, an average validation score of 3.36 was obtained for the mathematics LKS, categorized as "highly valid." This mathematics LKS covers essential topics such as selling and buying prices, profit and loss calculations, and discount concepts. Thus, the generated LKS possesses strong validity and emphasizes relevant materials within the context of social arithmetic.